2012
DOI: 10.1177/159101991201800306
|View full text |Cite
|
Sign up to set email alerts
|

Initial Experience of Intracranial Aneurysm Embolization Using the Balloon Remodeling Technique with Scepter C, a New Double-Lumen Balloon

Abstract: The balloon remodeling technique (BRT) was designed for endovascular treatment of wide-necked intracranial aneurysms. To date, the balloon catheters available have had a single lumen and suitable guidewires ranging from 0.010 to 0.012 inches. We describe the first case of aneurysm embolization using the BRT with the new double-lumen balloon catheter, Scepter C®, navigable on a 0.014-inch wire, and discuss the benefit of such a device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
0
16
0
Order By: Relevance
“…6 Twenty-two percent were poor-grade patients (HH grades IV and V) in the UCSF study, whereas 27% were poor-grade in our study. Several endovascular techniques are currently used, including double catheter, 11 balloon-assisted coiling, 12,13 and stent-assisted coiling techniques. 14,17 We used the balloon-assisted coiling technique in many cases (60.3%) without any significant increased complication rate compared with simple coiling, as reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Twenty-two percent were poor-grade patients (HH grades IV and V) in the UCSF study, whereas 27% were poor-grade in our study. Several endovascular techniques are currently used, including double catheter, 11 balloon-assisted coiling, 12,13 and stent-assisted coiling techniques. 14,17 We used the balloon-assisted coiling technique in many cases (60.3%) without any significant increased complication rate compared with simple coiling, as reported.…”
Section: Discussionmentioning
confidence: 99%
“…In unruptured cases, simple coiling, double-catheter coiling, 11 balloon-assisted, 12,13 or stent-assisted coiling 14 were used, depending on the neck size and aneurysm anatomy. In some cases of stent use, we used the balloon-assisted technique before inserting a stent because it appeared that the balloon technique obtained denser packing because of the inherent difficulty of crossing the stent struts in the first instance or in regaining access into the aneurysm.…”
Section: Endovascular Proceduresmentioning
confidence: 99%
“…Balloon and stent-assisted techniques have widened the indications for endovascular treatment of aneurysms with a wide neck and/or unfavorable anatomy that were otherwise unsuitable for coiling. [8][9][10] However, endovascular treatment of such complex intracranial aneurysms requires the use of complex endovascular techniques with double-stent placement in Y and X configurations. Bartolini et al 11 suggested that Y and X stent-assisted coiling was associated with a high rate of complications, 10% procedure-related permanent morbidity, and 1% mortality rate.…”
mentioning
confidence: 99%
“…The balloon remodeling technique is the other option appli- cable to treat wide-neck aneurysms [2][3][4] ; it had a higher rate of adequate postoperative occlusion than did standard coiling with comparable safety 17 and had the advantage to overcome antiplatelet therapy. However, in our case series, we focused on wideneck intracranial aneurysms in which the balloon remodeling technique had failed (patients 1 and 7) or was thought technically challenging because of the difficulty of navigating the balloon across the aneurysm neck.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous devices, including remodeling balloons [2][3][4] and stents, 5 have been developed to assist the endovascular treatment of wide-neck aneurysms. However, such techniques carry a great risk of hemorrhagic complications if they are applied in the acute phase of SAH because of the need for dual antiplatelet therapy.…”
mentioning
confidence: 99%